SULTAN (SEPATU SENSOR UNTUK LANGKAH TUNANETRA) - Latifah, Indriani; Sholahuddin, Asep; Maulana, Ridwan; Ismail, Firda Tubagus; Rahma, Putri Nazilatu (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The blinds, or the sight-impaired people, frequently undergo difficulties to run their daily lives owing to their disabilities. Yet, those troubles can luckily be minimized or even solved by the help of the technological developments. Therefore, on behalf of helping them, we have created SULTAN (Sensor shoes for the blinds), a shoes modified with Bluetooth and distance sensor functioned as a device to determine distance of an object and also a hole that may exists in front of the user. These technological shoes help the blinds to easily know any objects in front of them by simply wearing the shoes just like the normal people do. Experiment is the implementation method we use in which its steps are observation, study literature, GPS and sensor formula as a detector, jdesign the shoes as well as the tools, and the shoesâ test. The result of such a method is the making of the distance-detector tools for detecting things, holes, or even humans, in the different position based on the distance adjusted in the program. Besides that, SULTAN can likewise work as a detector for the blinds know the place or position they are in. Accordingly, based on the simulations we have tried, it can be thus concluded that this SULTAN shoes can be well functioned as a solution for the disabilities owned by the sight-impaired people.Keywords: SULTAN, Sensor, GPS